2019
DOI: 10.1111/cpr.12705
|View full text |Cite|
|
Sign up to set email alerts
|

PRRX1‐induced epithelial‐to‐mesenchymal transition in salivary adenoid cystic carcinoma activates the metabolic reprogramming of free fatty acids to promote invasion and metastasis

Abstract: Objectives: Increasing evidences demonstrate a close correlation between epithelialto-mesenchymal transition (EMT) induction and cancer lipid metabolism. However, the molecular mechanisms have not been clarified. Materials and methods:In our study, the relative expression level of PRRX1 was detected, its relationship with free fatty acid (FFA) and PPARG2 was analysed in 85 SACC tissues and 15 salivary glands from the benign salivary tumours. We also compared the FFAs composition and levels in these SACC cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…As a transcription factor, PRRX1 can bond to the promoter sequence (5′-AGCCCTTCACTACTGTTGACTTCTC-3′) of PPARG2 to regulate its expression. 5 Also, PRRX1b can bond to SOX9 promoter in a highly conserved sequence (5′-AACAAATTACA-3′). 4 As a transcription co-activator, PRRX1 can bind to PRRX2 in order to regulate MIR875 at the 5′-AATTA-3′ region of its promoter.…”
Section: Introductionmentioning
confidence: 99%
“…As a transcription factor, PRRX1 can bond to the promoter sequence (5′-AGCCCTTCACTACTGTTGACTTCTC-3′) of PPARG2 to regulate its expression. 5 Also, PRRX1b can bond to SOX9 promoter in a highly conserved sequence (5′-AACAAATTACA-3′). 4 As a transcription co-activator, PRRX1 can bind to PRRX2 in order to regulate MIR875 at the 5′-AATTA-3′ region of its promoter.…”
Section: Introductionmentioning
confidence: 99%
“…Although there was lack of the research focused on the relationship between FASN and PRRX1, our previous data showed that PRRX1 participated in the reprogramming of fatty acid metabolism in SACC. 32 Besides, our previous study showed that PRRX1 contributed to EMT via miR-642b-3p in head and neck squamous cell carcinoma (HNSCC). 33 Chen et al 34 of β-catenin, showed enhanced levels after the activity of Wnt/βcatenin pathway 38,39 and played a critical role in the EMT of cancers including pancreatic cancer, 40 NSCLC 41 and oral squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, our data demonstrated that the PRRX1 mediated the FASN‐induced EMT in SACC. Although there was lack of the research focused on the relationship between FASN and PRRX1, our previous data showed that PRRX1 participated in the reprogramming of fatty acid metabolism in SACC 32 . Besides, our previous study showed that PRRX1 contributed to EMT via miR‐642b‐3p in head and neck squamous cell carcinoma (HNSCC) 33 .…”
Section: Discussionmentioning
confidence: 99%
“…In this trial, it is possible that a higher dose of x-rays with an electron boost in the control arm might have produced the same result. The actual tumour RBE, which was probably higher than that used in the prescription since the adenoid cystic carcinomas used in the trial, was very slow growing, but some tumours may contain a high fatty acid concentration, which could increase neutron KERMA (24). Relatively superficial air sinus cancers were also thought to be better controlled by neutron therapy, although there was always concern that neutrons were particularly damaging to the underlying brain tissues, where it had been identified previously at Hammersmith that the white matter RBE was around 5 rather than 3, again for reasons already identified above.…”
Section: Other Neutron Therapy Studiesmentioning
confidence: 97%